Thinking about thinking about time. (2019) - Redshaw, Jonathan; Bulley, Adam; Suddendorf, Thomas
Abstract: Hoerl & McCormack (H&M) discuss the possible function of meta-representations in temporal cognition but ultimately take an agnostic stance. Here we outline the fundamental role that we believe meta-representations play. Because humans know that their representations of future events are just representations, they are in a position to compensate for the shortcomings of their own foresight and to prepare for multiple contingencies.